Total Serum Cholesterol Level in Cases of Carcinoma Breast – A Correlative Study - Kafil Akhtar (Journal of Advanced Laboratory Research in Biology, 2012)
Aims and Objective: Correlation between serum cholesterol level and risk of breast cancer.